From Waste to Crisis: The Environmental Security Implications of Jogja Waste Emergency - Ilham Agustian Candra (Politicos: Jurnal Politik Dan Pemerintahan, 2025)
There is a critical waste management crisis in the Special Region of Yogyakarta (DIY) that is popularly referred to as the Darurat Sampah Jogja (Jogja Waste Emergency). The crisis has exacerbated existing problems in waste management and also resulted in devastating environmental effects. The purpose of this study is to examine the degree to which the Jogja Waste Emergency has influenced the environmental impacts on the citizens of Yogyakarta City. This research sheds light on the complex risks of inefficient waste management and their extensive effects through the paradigm of human security, notably in environmental security. The work adopts a qualitative research design consisting of primary and secondary data sources. Primary data are gathered based on in-depth interviews with the primary informants of various background categories among members of affected communities. Simultaneously, secondary data is gathered from policy documents, government and non-government reports, as well as media reports, which all help to contextualize and reinforce the findings. The analysis suggests that the Jogja Waste Emergency was first seen as a crisis marked by the accumulation of waste, and foremost manifesting immediate threat of environmental degradation, health, and disaster risk. But as the issue worsens, wider and more complicated impacts are shown, especially with regard to the pollution of essential natural resources like air and water. Such environmental degradation interferes with daily life, endangering public well-being and stability in urban Yogyakarta. The research stresses the need for comprehensive reforms in waste management, enforcement of stronger policy interventions, and more community involvement to address and minimize the environmental security threats presented by this chronic crisis.